Faculty development efforts to promote screening, brief intervention, and referral to treatment (SBIRT) in an internal medicine faculty-resident practice. Issue 1 (2nd January 2017) - Stone, Alanna; Wamsley, Maria; O'Sullivan, Patricia; Satterfield, Jason; Satre, Derek D.; Julian, Katherine
ABSTRACT: Background : Screening, brief intervention, and referral to treatment (SBIRT) is a practical means to address substance misuse in primary care. Important barriers to implementing SBIRT include adequacy of training and provider confidence as well as logistical hurdles and time constraints. A faculty development initiative aimed at increasing SBIRT knowledge and treatment of substance use disorders (SUDs) should lead to increased use of SBIRT by faculty and the residents they teach. This study examined how a faculty development program to promote SBIRT influenced faculty practice and resident teaching. Methods : This was a cross-sectional study of faculty exposed to multiple SBIRT educational interventions over a 5-year period in an academic faculty-resident general medicine practice. Participants completed a brief online survey followed by a semistructured interview. Quantitative responses were examined descriptively. Qualitative questions were reviewed to identify key themes. Results : Fifteen of 29 faculty (52%) completed the survey and 13 (45%) completed the interviews regarding faculty development interventions. Faculty thought that SBIRT was an important skill and had confidence in screening for substance use disorders, although confidence in making treatment referrals and prescribing pharmacotherapy were rated lower. Many faculty reported screening more frequently for SUDs after attending faculty development sessions. However, several reported that the training did not improve their SBIRT teaching to residents during clinic precepting sessions. To improve uptake of SBIRT, a majority of faculty recommended electronic health record (EHR) alerts. Conclusions : SBIRT is a highly valued set of skills, and training may enhance rates of screening for substance misuse. However, participants did not report a substantial change in SBIRT teaching as a result of faculty development. In the future, small, targeted faculty development sessions, potentially involving strategies for using the electronic health record (EHR), may be an effective way to enhance primary care SBIRT skills.